Perinatal and Postnatal Outcomes of Fetal Cardiac Rhabdomyoma: A Single Center Experience of Six Year - Tuncer Can, Sevim (2024)
Introduction: Fetal cardiac tumors are rare and generally have a good prognosisdepending on location and size. Objective: To examine perinatal and postnataloutcomes along with ultrasound and genetic findings of fetal cardiac rhabdomyoma.Methods: This retrospective cohort study was conducted in a single tertiary center.Ten prenatally diagnosed cases of fetal cardiac rhabdomyoma were included inthe study. The data obtained included maternal characteristics, gestational age atdiagnosis, echocardiographic features including tumor size, number and location,other antenatal ultrasound findings, genetic and pathological examinations,gestational age at birth, neonatal outcomes, and postnatal long-term outcomes.Results: In half of the cases (five), multiple tumors were detected sonographically.Tumor sizes ranged from 5 to 38 millimeters (mm). Four (40%) of the cases hadadditional cardiac anomalies such as right ventricular hypoplasia, left ventricularhypoplasia and pericardial effusion. Additionally, hydrops fetalis was detected inthree (30%) cases. One case died at 26 weeks gestation. One case was terminated atthe request of the family due to the detection of a mutation in the tuberous sclerosiscomplex (TSC) gene. Hydrops fetalis was significantly more common in cases withfetal and neonatal deaths (60% vs. 0%; p=0.038). The TSC gene mutation was notassociated with fetal and neonatal deaths. TSC gene mutation was detected in4 of the cases (40%) and there was a family history in one of these cases (25%).Conclusion: Fetal cardiac rhabdomyomas can cause prenatal and postnatal deathsdue to heart failure. Furthermore, fetal rhabdomyomas are associated with TSCregardless of family history.